Assessment of the relationship between the international roughness index and dynamic loading of heavy vehicles. Issue Volume 18:Issued 8(2017) (3rd August 2017) - Bilodeau, Jean-Pascal; Gagnon, Louis; Doré, Guy
Abstract: Due to imperfect surface profiles, heavy vehicles moving at high speed on flexible pavement structures oscillate in the vertical axis. This phenomenon induces dynamic loads, which oscillate at lower and higher values than the average load associated with static load considered with most pavement analysis and design applications. Higher loads applied to flexible pavements are likely to significantly reduce pavement service life. A new multibody dynamic truck model was used to study heavy vehicle wheel load for various pavement profiles of varying international roughness index (IRI ). The modelled heavy vehicle wheel load response were used to calculate the dynamic load coefficient, and a relationship withIRI was proposed. On the basis of this relationship, the evolving pavement surface profile, and thus evolvingIRI, was used to determine the evolution of dynamic loading with pavement life. A comparison of pavement service life for the classical static loading and for dynamic loading was made for three highway flexible pavement structures. When dynamic loads are considered, it was found that the pavement service life reduction may be reduced of about 29 and 20% for bottom-up fatigue cracking and structural rutting failure criteria.